Assessing Policy Implementation: A Study of the Balikpapan Mayor Regulation No. 16/2015 on Civil Servant Work Area Transfers - Evi Nurhayanti; Aji Ratna Kusuma; Santi Rande (Jurnal Pemerintahan dan Politik Lokal, 2026)
This study aims to examine the implementation of Balikpapan Mayor Regulation Number 16 of 2015 concerning the transfer of civil servant work areas and its implications for organizational effectiveness and apparatus performance as part of efforts to organize human resources for civil servants at the regional level. This study uses a qualitative approach with descriptive analysis through data collection in the form of in-depth interviews, observations, and reviews of policy documents and related personnel documents. The results of the study indicate that normatively the regulation has provided quite clear guidelines regarding the procedures and mechanisms for transferring ASN work areas, however, in practice its implementation is still faced with various administrative and institutional challenges, such as limited institutional capacity, bureaucratic complexity, and suboptimal coordination between work units. The process of transferring work areas also requires employees to adapt to the new work environment which in the initial stages has the potential to affect the stability of individual and organizational performance. Nevertheless, in the long term, the policy of transferring work areas has positive implications, especially in the distribution of workloads, adjusting competencies to organizational needs, and increasing the effectiveness of work unit performance. The success of this policy is highly dependent on institutional support, clarity of assignments, and post-transfer development mechanisms, so that policy implementation is not only determined by regulatory clarity, but also by organizational capacity and the quality of sustainable administrative governance.